2015
DOI: 10.1002/ejsp.2041
|View full text |Cite
|
Sign up to set email alerts
|

Would you post that picture and let your dad see it? Culture, honor, and Facebook

Abstract: Honor means "high respect; esteem," but it has different associations for different cultures. In honor cultures (Turkey), esteem depends on one's own perception of self-worth and on other people's opinions. In those cultures, honor is easily lost and difficult to regain. In dignity cultures (northern America), esteem mainly depends on the individual and cannot be taken away by others. One way to lose honor in Turkey is through behaviors that may be seen as "potentially improper." Thus, we expected that posting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…This media report discusses how private Facebook messages and status updates were submitted as evidence in a court case: https://www.youtube.com/watch?v=iDdKr3dkc4g 11. Günsoy et al (2015) found that Turks (an honor culture similar to Azerbaijani) had greater self-censorship of social media content than Americans, significantly explained by concern for honor. 12. http://www.katypearce.net/facebook-users-in-april-and-july-2015-in-azerbaijan-accordingto-facebook/ 13.…”
Section: Discussionmentioning
confidence: 95%
“…This media report discusses how private Facebook messages and status updates were submitted as evidence in a court case: https://www.youtube.com/watch?v=iDdKr3dkc4g 11. Günsoy et al (2015) found that Turks (an honor culture similar to Azerbaijani) had greater self-censorship of social media content than Americans, significantly explained by concern for honor. 12. http://www.katypearce.net/facebook-users-in-april-and-july-2015-in-azerbaijan-accordingto-facebook/ 13.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, members of our team have also investigated honour-related behaviour in the context of social media use. GŸnsoy, Cross, Sarõbay, Olcaysoy-…kten, and Kurutaş (2015) hypothesized that Turkish young people would be less likely than American young people to post pictures or information on Facebook (a widely used social media platform at the time) that was potentially harmful to their reputation or that would expose them to gossip. In Turkish (Uskul et al, 2012), Turkish participants may have feared that relatives would be especially upset at seeing pictures that could be construed as dishonourable.…”
Section: --------------------------mentioning
confidence: 99%
“…However, we predicted that shame responses would be affected by the public versus private nature of the insult when an honor-oriented identity was threatened, as shame may be more reflective of the externally ascribed element of honor which is only lost when other people know about the stain to the individual or groups' image (see Günsoy, Cross, Saribay, Olcaysoy Ökten, & Kurutaş, 2015, for other ways people mask transgressions from the public eye). Thus, if the student identity was insulted, we predicted low levels of shame overall, because as a low-honor identity, it should be impervious to insult.…”
Section: Studymentioning
confidence: 99%